Analisis Jaringan Produksi Dan Inovasi Varian Rasa Pada Kue Sus Choux - Evi Ulviah; Resya Dwi Marselina (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Building a business network is a crucial business strategy during the startup process. Business networking refers to relationships formed through various interactions among business players, professionals, and potential financial specialists (Ferira, 2023). While some studies have explored business networks, such as the analysis of TikTok as a platform for millennial business networking, there hasn't been specific research on production networks, which is a derivative of business networks. To address this gap and the literature void regarding production networks, the author proposes a scholarly title, "Analysis of Production Networks and Innovative Flavor Variants in Choux Pastry Puffs," with the goal of understanding production networks. Supply Chain Management (SCM) involves planning, management, and product activation, utilizing cost-effective strategies for controlled efficiency and increased profits (Hastari, 2023). According to Lukman (2021, p. 7), "Choux Pastry Puffs" fall into the moist cake category and are favored by sweet enthusiasts. Choosing it as a brand aims for easy recall and customer attraction, serving as a promotional strategy. The procurement of Choux Pastry Puffs' raw materials is simple, without signed contracts with suppliers; materials are directly purchased from a convenience store. While "Choux Pastry Puffs" is not native to Indonesia, innovation is expected to cater to diverse tastes. Analyzing production networks and innovative flavor variants in Choux Pastry Puffsaims not only to fulfill coursework requirements but also to open new business opportunities and attract public attention.